Omics approaches - Comprehensive insights for abiotic stress tolerance in horticultural crops - Bharathi, A; Vijai, S K S; Karthikeyan, J; Agalya, P; Rajiv, P (Plant Science Today, 2025)
Abiotic stress tolerance in plants can be better understood and enhanced through the use of omics techniques, which entail the extensive study of biological molecules. Drought, salt, temperature fluctuations and heavy metal toxicity are examples of abiotic stresses that can drastically lower the output of agriculture. Researchers identified the molecular mechanisms behind plant responses to these stresses and created plans for enhancing agricultural stress tolerance by utilizing a variety of omics technologies, including phenomics, proteomics, metabolomics, transcriptomics and genomics. Researchers are now able to clarify the molecular expressions behind the difficult-to-understand plant stress responses because of the advancements in omics methods and technology. CRISPR-Cas9 genome editing has the ability to overexpress resilience factors or wipe out susceptibility genes. Regulatory networks governing stress-adaptive pathways were revealed by RNA-Seq. In order to lessen the consequences of stress, proteomics found proteins that had been activated by post-translational modifications. Osmoprotectants and signaling molecules produced during acclimation were discovered by metabolomics. Stress tolerance marker-trait connections have been found using "quantitative trait locus mapping." Climate resilience can be increased by introducing wild genes into crops. Crosstalks across stress tolerance pathways are being uncovered by combining these omics using systems biology modeling. In order to maintain food and nutritional security, the development of climate-resilient horticultural crops will be supported by ongoing omics developments.